Analisis Penerapan Bauran Pemasaran Pada Produk Jasa di KSPPS Karisma Cabang Grabag - Lasnia, Hani (Politeknik Negeri Ambon, 2021)
Marketing is an exchange process that is carried out to fulfill human wants and needs. Marketing activities are very important activities for companies to achieve success, so companies must be able to introduce and promote their products to the wider community by using good strategies to win consumers. The strategy used in KSPPS Karisma Grabag Branch is to use a marketing mix consisting of 4P namely Product, Place, Process and Promotion. The purpose of this research is to find out how the application of the marketing mix of the service products used by KSPPS Karisma Grabag Branch. The method used is descriptive qualitative research methods with qualitative data types. Sources of data used are primary data derived from the process of observation and interviews as well as secondary data from articles, files and the internet. Data collection techniques used are through observation, interviews and documentation. Data collection techniques using data reduction, data display or data presentation and finally is the verification of data or conclusions with triangulation techniques. From the data and research that has been done by researchers shows that the marketing mix used by KSPPS Karisma Grabag Branch is considered effective in introducing and promoting various products because it is able to increase the number of customers and win the competition as evidenced by the increasing number of customers using KSPPS Karisma services. The mix used by KSPPS Karisma Grabag Branch is product, place, process and promotion. This marketing mix is very important to win the competition, get new customers and retain old customers, develop the company, maintain the viability of the company and get profits.